Komparasi Metode Case Based Reasoning dan Certainty Factor Kasus Penyakit Gigi Mulut - Suryo Atmojo; Ruli Utami; Suzana Dewi; Nurwahyudi Widhiyanta (SMATIKA JURNAL : STIKI Informatika Jurnal, 2023)
Dental and oral disease is one of the diseases that has a serious impact on human health in general, because the teeth and mouth are the initial entry for germs and bacteria. Many people underestimate this disease so that treatment is carried out when the condition is severe. Dental and oral health also affects overall health. Therefore, it is important to check your teeth and mouth regularly. The Certainty Factor and Case Based Reasoning methods are used to diagnose website-based dental and oral diseases. This research will create a website-based dental and oral disease expert system that aims to make it easier for users to diagnose dental and oral diseases. The results of this study reveal that dental and oral diseases are classified into twenty types with ninety symptoms, and each of the two methods has a different level of speed and accuracy. However, each method also has its own advantages and disadvantages, the results of the diagnosis of the Certainty Factor method are 0.20 to 0.30 seconds faster in providing diagnostic results compared to the Case Based Reasoning method and the Certainty Factor method also has superior accuracy results of 84% while the Case Based Reasoning produces 51% accuracy